Mediated Muslim cosmopolitanism: new media and popular culture engagements in Brunei and Malaysia - Siti Mazidah Haji Mohamad (Routledge studies on Islam and Muslims in Southeast Asia, 2025)
"Mohamad examines the day-to-day experience of virtual and non-tangible mobilities of young Bruneian Malay Muslim and Malaysians, as enabled by popular culture and digital media. Cosmopolitanism has garnered interest from sociology, political studies, religious studies, geography, and education scholars. Despite this, there are three gaps in the study of Muslim cosmopolitanism. Firstly, young Muslims' cosmopolitanism in the digital age has not been intensively studied. Secondly, existing research overlooks Southeast Asia, especially Brunei Darussalam. Thirdly, the focus has not sufficiently engaged with popular culture and new media. This book addresses these gaps by exploring the everyday lives of Bruneian Malay Muslim and Malaysian youths, shaped by local, transcultural, and global practices. It expands the Muslim cosmopolitanism concept by examining the daily concerns, challenges, and practices these youths experience, offering new forms of mediated Muslim cosmopolitanism. Grounded in robust empirical data from two extensive research projects (2010-2024), the book employs diverse research approaches (ethnography and phenomenology) and methods (Qualitative Content Analysis and Interviews), ensuring reliable and in-depth findings. Scholars in geography, sociology, religious studies, and youth studies will find this book invaluable for its insights into cosmopolitanism, popular culture, new media, digital youth, and contemporary Southeast Asia"--